1996
DOI: 10.1007/bf01980770
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition of some analgesic agents

Abstract: Thermogravimetry, derivative thermogravimetry (TG, DTG) and differential scanning calorimetry (DSC), were used to study the thermal behaviour of mefenamie acid, ibuprofen, acetaminophen, sodium diclofenac, phenylbutazone, dipyrone and salicylamide. The results led to thermal stability data and also to the interpretation concerning the thermal decomposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 7 publications
3
20
1
Order By: Relevance
“…We were unable to detect such sharp endothermic peaks prior to the melting peak under dynamic flow of neither He nor N 2 , and under synthetic air such peak did not appear at all. Our data contradicts the suggestion made by Ribiero et al 1) regarding a polymorphic transition at temperature 280°C. We hypothesize that this first broad based endothermic peak detected in our DSC thermograms appeared as a result of formation of a new compound during the heating process, and the chances of forming this new compound become higher when slow scanning rates are used due to kinetics of the process.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…We were unable to detect such sharp endothermic peaks prior to the melting peak under dynamic flow of neither He nor N 2 , and under synthetic air such peak did not appear at all. Our data contradicts the suggestion made by Ribiero et al 1) regarding a polymorphic transition at temperature 280°C. We hypothesize that this first broad based endothermic peak detected in our DSC thermograms appeared as a result of formation of a new compound during the heating process, and the chances of forming this new compound become higher when slow scanning rates are used due to kinetics of the process.…”
Section: Discussioncontrasting
confidence: 57%
“…The T m temperatures of 283-284°C and 288-289°C obtained at scanning rates of 10°C/min and 20°C/min, respectively, for the endothermic peak are in close agreement with literature reports for the melting point of diclofenac sodium. 1,6) The double peak phenomenon observed in the thermograms obtained under both He and N 2 is of specific interest. Ribeiro et al 1) reported that a sharp endothermic peak (at 280°C) occurred in DSC thermograms for samples of diclofenac sodium under static atmospheric air prior to the melting peak (at 285°C), and postulated that the peak was due to a polymorphic transition of the material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wendlandt and Collins [2] used DTA and TG as aids in the characterization and identification of commercial non-preescription analgesics. Other investigations of the use of thermoanalytical techniques for the study of drug substances and for applications in routine pharmaceutical analysis and in the pharmaceutical industry have also been described [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Wendlandt and Collins 2 used DTA and TG thermal analysis techniques as aids in the characterization and identification of commercial non-preescription analgesics. Other investigations of the use of thermal analysis techniques for the study of drug substances and for applications in routine pharmaceutical analysis and in the pharmaceutical industry have also been described [3][4][5][6][7][8][9][10][11][12][13][14][15][16] . No reference has been found on the application of TG and DSC in the study of trimethoprim, sulfamethoxazole, ampicillim, tetracycline hydrochloride, rifampim and association of sulfamethoxazole with trimethoprim.…”
Section: Introductionmentioning
confidence: 99%